Developing and applying a classification system for ranking the biological effects of endocrine disrupting chemicals on male rockfish Sebastiscus marmoratus in the Maowei Sea, China. (February 2021) - Zheng, RongHui; Fang, Chao; Hong, FuKun; Kuang, WeiMing; Lin, Cai; Jiang, YuLu; Chen, JinCan; Zhang, YuSheng; Bo, Jun
Abstract: Endocrine disrupting compounds (EDCs) in marine environments has become a major environmental concern. Nonetheless, the biological effects of EDCs on organisms in coastal environments remain poorly characterized. In this study, biomonitoring of EDCs in male fish Sebastiscus marmoratus was carried out in the Maowei Sea, China. The results showed that the concentration of 4-nonylphenol (4-NP) was below the detection limit, the concentrations of 4-tert-octylphenol (4-t-OP) and bisphenol A (BPA) in seawater were moderate compared with those in other global regions, and the possible sources are the municipal wastewater discharge. Nested ANOVA analyses suggest significant differences of the brain aromatase activities and plasma vitellogenin (VTG) expression between the port area and the oyster farming area. A new fish expert system (FES) was developed for evaluating the biological effects of EDCs on fish. Our findings show that the FES is a potential tool to evaluate the biological effects of marine pollutants. Highlights: Multiple biomarkers were employed for biomonitoring of EDCs in male S. marmoratus . A Fish Expert System (FES) was developed to integrate and interpret biomarker data. The FES objectively ranked the level of the EDC-induced biological effects on fish. FES is a potential tool to evaluate the biological effects of marine pollutants.